Ginger and Lemon Aromatherapy Enhances Learning Concentration in Midwifery Students: A Randomized Controlled Trial - Laila, Laila; Lisa, Ulfa Farrah; Nofila, Hanifah; Taufia, Dina; Az-zahra, Salsabila; Azzahra, Halsya Zahra; Hussain, Altaf; Mehtab, Mehtab (JIK-JURNAL ILMU KESEHATAN, 2025)
Background: Focus is the main thing for learning, but students still come across distractions in their environment, anxiety, and mental fatigue. Essential oil aromatherapy may improve cognitive functions through neurophysiological mechanisms.Objective: To find out if the combination of ginger and lemon essential oils would help concentration of midwifery students during self-directed learning.Methods: 92 Andalas University midwifery students were randomly assigned to two groups; experimental (aromatherapy, n=46) and control (n=46). The ginger- lemon aromatherapy (40:60 ratio) was given to the experimental group by a ultrasonic diffuser during four weekly 90-minute tutorials. Concentration was determined through a 20-item questionnaire that was validated and which assessed motivation, sustained attention, anxiety regulation, comprehension efficiency, and distraction resistance.Results: Concentration of the experimental group raised significantly from 2.388 to 4.243 (p<0.001, Cohen's d=14.52), whereas the control group did not show any change (p=0.075). The main changes: 37% of the distraction resistance was increased, 23% of the comprehension efficiency was enhanced, and 10% of the anxiety was reduced.Conclusion: Ginger-lemon aromatherapy is an effective way to hype up concentration in learning from different angles by the synergistic anxiolytic and cognitive-stimulating mechanisms, thus giving a simple, cheap educational intervention.